Interactions between amphibians' symbiotic bacteria cause the production of emergent anti-fungal metabolites - Loudon, Andrew H.; Holland, Jessica A.; Umile, Thomas P.; Burzynski, Elizabeth A.; Minbiole, Kevin P. C.; Harris, Reid N. (Frontiers in Microbiology, 2014)
Amphibians possess beneficial skin bacteria that protect against the disease chytridiomycosis by producing secondary metabolites that inhibit the pathogen Batrachochytrium dendrobatidis (Bd). Metabolite production may be a mechanism of competition between bacterial species that results in host protection as a by-product. We expect that some co-cultures of bacterial species or strains will result in greater Bd inhibition than mono-cultures. To test this, we cultured four bacterial isolates (Bacillus sp., Janthinobacterium sp., Pseudomonas sp. and Chitinophaga arvensicola) from red-backed salamanders (Plethodon cinereus) and cultured isolates both alone and together to collect their cell-free supernatants (CFS). We challenged Bd with CFSs from four bacterial species in varying combinations. This resulted in three experimental treatments: 1) CFSs of single isolates; 2) combined CFSs of two isolates; and 3) CFSs from co-cultures. Pair-wise combinations of four bacterial isolates CFSs were assayed against Bd and revealed additive Bd inhibition in 42.2% of trials, synergistic inhibition in 42.2% and no effect in 16.6% of trials. When bacteria isolates were grown in co-cultures, complete Bd inhibition was generally observed, and synergistic inhibition occurred in four out of six trials. A metabolite profile of the most potent co-culture, Bacillus sp. and Chitinophaga arvensicola, was determined with LC-MS and compared with the profiles of each isolate in mono-culture. Emergent metabolites appearing in the co-culture were inhibitory to Bd, and the most potent inhibitor was identified as tryptophol. Thus mono-cultures of bacteria cultured from red-backed salamanders interacted synergistically and additively to inhibit Bd, and such bacteria produced emergent metabolites when cultured together, with even greater pathogen inhibition. Knowledge of how bacterial species interact to inhibit Bd can be used to select probiotics to provide amphibians with protection against Bd.